2008
DOI: 10.1100/tsw.2008.47
|View full text |Cite
|
Sign up to set email alerts
|

Acid Rain Phenomenon in Niger Delta Region of Nigeria: Economic, Biodiversity, and Public Health Concern

Abstract: Rain samples were collected from Warri and Port Harcourt, two major oil-producing cities of Nigeria in April-June, July-August, and September-October 2005 and 2006. Awka, a “non-oil” city was used as control. Samples were collected from three points, using clean plastic basins fastened to a table, 2 m above ground level and 115 m away from tall buildings and trees. Water samples were filtered and acidity determined using digital pHmeter. The results show that the rain samples were acidic. The pH values for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…The rapid urbanization and industrialization of the Niger Delta Region of Nigeria occasioned by huge crude oil and gas reserves has had its toll on the environment (Nduka et al 2008). The US Department of Energy estimates that since 1960, there has been more than 4,000 oil spills, discharging several million barrels of crude oil into the ponds, ditches, creeks, beaches, streams, and rivers of the Niger Delta (Amaize 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid urbanization and industrialization of the Niger Delta Region of Nigeria occasioned by huge crude oil and gas reserves has had its toll on the environment (Nduka et al 2008). The US Department of Energy estimates that since 1960, there has been more than 4,000 oil spills, discharging several million barrels of crude oil into the ponds, ditches, creeks, beaches, streams, and rivers of the Niger Delta (Amaize 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Over 2.5 billion Fe 3 of crude-associated gas is flared in Nigeria daily with an estimated yearly financial loss of $2.5billion. Acid rain pre-cursor gases -NO 2 and SO 2 are products of high temperature reactions and gas flaring in the study, area makes this possible, hence we have reported acid rain in our previous studies (Nduka et al 2008, Nduka and Goldberg, 1985) which normally give rise to black rain in Niger-delta region of Nigeria is one of the major components of air pollution worldwide.…”
Section: Air Pollution Resulting From Crude Oil Refining and Gas Flaringmentioning
confidence: 99%
“…1). Ten (10) water samples from boreholes were collected from the selected areas using Global Positioning System (GPS) to locate the points [8][9][10]. Well logs from the ten (10) wells were obtained from which a fence diagram (a 3 dimensional diagram) indicating various aquifer and their stratigraphy in three (3) dimension at the surface, [11].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier researchers who worked on the soils of Onitsha and environs reported high concentration of the soil parameters which they investigated; the high concentration was attributed to the presence of dumpsite, effluent discharge, industrial and sewage discharge and other anthropogenic activities within the area of study. The leachate from these materials affects the quality of groundwater due to infiltration and percolation [8][9][10]. The geology of the study area fall within the Anambra basin in south eastern Nigerian, [21][22][23][24][25][26] The present work is to consolidate the existing work and critically examine the chemistry and the water portability of the middle aquiferous horizon, been the most tapped aquifer in the study area; this is important with the view of the fact that water is a universal solvent that we cannot do without in our daily activities.…”
mentioning
confidence: 99%